The Ugi reaction in polymer chemistry: syntheses, applications and perspectives - Yang, Bin; Zhao, Yuan; Wei, Yen; Fu, Changkui; Tao, Lei (Polymer chemistry, 2015)
The Ugi reaction, one of the most famous multicomponent reactions, has recently been introduced into polymer chemistry as a novel, efficient and useful tool to prepare multifunctional polymers. In this review, the recent progress on the utilization of the Ugi reaction in polymer chemistry, including monomer synthesis, polycondensation, post-polymerization modification (PPM) etc . has been summarized. Meanwhile, the applications of the multifunctional polymers synthesized via the Ugi reaction and the future development of the Ugi reaction in polymer chemistry have also been discussed. The well-known Ugi reaction is becoming a novel, efficient and useful tool to prepare multifunctional polymers.